Controlling the selectivity of an intramolecular Friedel–Crafts alkylation with alkenes using selenium under mild conditions. Issue 21 (19th March 2020) - Liao, Ming-Hong; Zhang, Meng; Hu, Dai-Hui; Zhang, Rui-Han; Zhao, Yan; Liu, Shan-Shan; Li, Yun-Xia; Xiao, Wei-Lie; Tang, E
Abstract : An efficiently divergent intramolecular Friedel–Crafts alkylation by unactivated alkenes with seleniranium ion-controlled Markovnikov/ anti -Markovnikov specificities under mild conditions has been investigated. Abstract : An efficiently divergent intramolecular Friedel–Crafts alkylation by unactivated alkenes with seleniranium ion-controlled Markovnikov/ anti -Markovnikov specificities under mild conditions has been investigated. 2-Benzoxepin, isochroman, and isochromene can be produced in one-pot procedures from the same substrate in high yields and with high regio- and stereospecificity. The products are challenging to access via 7- endo-trig carbocyclizations and by 7- endo-trig carbocyclization/rearrangement/6- exo-trig oxycyclization and 6- exo-trig carbocyclization/deselenenylation reaction sequences, respectively. Mechanistic experiments indicated that in addition to the stereospecific anti -addition processes of the cyclization reactions, the formation of a stable carbocation after ring opening of the seleniranium ion leads to an NPSP-mediated 7- endo-trig carbocyclization; the steric hindrance of the seleniranium intermediate controls the regioselectivity when using TPSCA at 60 °C, which promotes 6- exo-trig carbocyclization. Two distinct catalytic cycles were proposed, and the structures of transition states and products were identified by ab initio calculations and X-ray analyses.